Molecular Imaging of High-Risk Atherosclerotic Plaques: Is It Clinically Translatable? - Hwang, Byung-Hee (The Korean Society of Cardiology, 2011)
The explosive epidemics of diabetes and obesity as well as an aging population have led to cardiovascular diseases as the leading cause of world-wide morbidity and mortality beyond cancer. The recent introduction of drug-eluting stents and medications such as statins, dual anti-platelet therapy, and angiotensin converting enzyme inhibitors has dramatically improved clinical outcomes in patients with cardiovascular diseases. However, mortality is still increasing despite state-of-the-art therapeutics, as current diagnostic and therapeutic strategies against cardiovascular disease center on "locking the barn door after the horse has been stolen". Novel diagnostic solutions that identify individuals at risk before the disease is overt are needs. Imaging approaches that visualize molecular targets rather than anatomical structures aim to illuminate vital molecular and cellular aspects of atherosclerosis biology in vivo. Recent technological advances in small animal imaging systems and dedicated targeted/activatable molecular imaging probes have positioned molecular imaging to greatly impact atherosclerosis imaging in the next decade. However, several issues must be addressed before its clinical translation.